Działalność naukowa i edukacyjna archiwum kościelnego na przykładzie Archiwum Salezjańskiego Inspektorii Pilskiej - Wąsowicz, Jarosław (Archiwa, Biblioteki i Muzea Kościelne, 2014)
The Salesian Archive of the Province of Piła (ASIP) was founded when the new Salesian Province of Piła was created in December 1979. The most extensive group of records in this archive concerns the territorial and personnel development of the Province of Piła, its apostolic activities, property and history. The precious collections also include legacies. In recent years, the main part of the archive activities has been focused on organizing and describing the fonds. In the years 2004-2011 the Salesian Archive of the Province of Pila in collaboration with other institutions organized several exhibitions, which were well received. In the years 2005-2011 the archive organized or co-organized several symposia and academic conferences, including the all-Poland ones. During the period under discussion, the archive also dealt with publishing activities. Currently it releases two book series. The fi rst one, entitled Biographical series under the auspices of ASIP, includes publications presenting the priests: Lucjan Gieros SDB, Stanisław Olędzki SDB, Franciszek Miśki SDB and Stanisław Ormiński. In 2009, another series of publications was released: Studies and source materials under the auspices of the Salesian Archive of the Province of Piła. So far, there have been two publications containing materials from the symposia in Aleksandrów Kujawski and Szczecin. A new series was also created – Bibliographic Series under the auspices of ASIP.